ZnO thin films as propane sensors: Band structure models to explicate the dependence between the structural and morphological properties on gas sensitivity. (July 2017) - Gómez-Pozos, Heberto; Karthik, T.V.K.; de la L. Olvera, M.; Barrientos, Abel García; Cortés, Obed Pérez; Vega-Pérez, J.; Maldonado, A.; Pérez-Hernández, R.; Rodríguez-Lugo, V.
Abstract: Pure Zinc oxide (ZnO) thin films were deposited on soda-lime glass substrates by utilizing ultrasonic spray pyrolysis technique (USP) and tested them as propane sensors. Propane sensitivity increased with decrease in the substrate temperature and water content in the feedstock solution. XRD analysis confirms that, the (002) directional ZnO which correspond to the hexagonal wurzite structure. Also, formations of rose like and spherical structures were confirmed by the SEM analysis. X-ray photoelectron spectroscopy (XPS) confirms the presence of loosely bound oxygen atoms on the surface of the low water content substrates. Two energy band structure models were proposed and explicated in detail for analyzing the effect of structural, morphological and optical properties of ZnO thin films on propane sensing properties. Highest sensitivity (~10) was obtained for ZnO films deposited with the lowest water content, at a deposition temperature of 400 °C and operated at 200 °C. Highlights: Samples deposited at 450 °C consist of lesser ZnO structural defects. Samples with lower water content (1/100) has higher oxygen vacancies and loosely bound surface oxygen. Samples with lower water content (1/100) and deposited at 400 °C shower higher sensitivities around 10. Two physical energy structural models are proposed to interpret the propane sensing mechanism. The aging of films increased the sensitivity of the ZnO films.